Characterization of a functional Ca2+ toolkit in urine-derived stem cells and derived skeletal muscle cells. (May 2022) - Talmon, Maria; Massara, Erika; Pruonto, Giulia; Quaregna, Martina; Boccafoschi, Francesca; Riva, Beatrice; Fresu, Luigia Grazia
Highlights: Urine stem cells and derived skeletal muscle cells express pluripotent and skeletal muscle markers, respectively. In urine stem cells ATP-induced Ca 2+ entry is IP3 dependent and supported by ROCE machinery. In derived skeletal muscle cells Ca 2+ transients are IP3, RyR and l -type VOCC-dependent. Abstract: Muscular diseases are characterized by a wide genetic diversity and the Ca 2+ -signalling machinery is often perturbed. Its characterization is therefore pivotal and requires appropriate cellular models. Muscle biopsies are the best approach but are invasive for the patient and difficult to justify if the biopsy is not for diagnostic purposes. To circumvent this, interest is mounting in urine-derived stem cells that can be differentiated into skeletal muscle cells. In the present study, we isolated stem cells from urine (USC) samples of healthy donors and differentiated them by MyoD lentiviral vector transduction into skeletal muscle cells (USC-SkMC). As expected, USCs and USC-SkMCs are characterized by a radically different pattern of expression of stem and skeletal muscle markers. Characterization of cells in the present manuscript focused on Ca 2+ -signalling. Undifferentiated and differentiated cells differed in the expression of key proteins involved in Ca 2+ -homeostasis and also displayed different Ca 2+ -responses to external stimuli, confirming that during differentiation there was a transition from a non-excitable to an excitable phenotype. In USCs, the main mechanism of calcium entry was IP3 dependent, suggesting a major involvement of receptor-operated Ca 2+ entry. Indeed, U-73122 (a PLC inhibitor) significantly inhibited the Ca 2+ increase triggered by ATP both in calcium and calcium-free conditions. In USC-SkMCs both store- and receptor-operated calcium entry were active. Furthermore, a caffeine challenge led to Ca 2+ release both in the presence or absence of extracellular calcium, which was inhibited by ryanodine, suggesting the presence and functionality of ryanodine receptors in USC-SkMCs. Lastly, the voltage-operated calcium channels are operative in USC-SkMCs, unlike in USCs, since stimulation with high concentration of KCl induced a significant calcium transient, partially reversed by verapamil. Our data therefore support the use of skeletal muscle cells derived from USCs as an easily amenable tool to investigate Ca 2+ -homeostasis, in particular in those (neuro)muscular diseases that lack valid alternative models. Graphical abstract: Image, graphical abstract